Fullerene derivatives with oligoethylene–glycol side chains: an investigation on the origin of their outstanding transport properties. Issue 45 (25th August 2021) - Dong, Jingjin; Sami, Selim; Balazs, Daniel M.; Alessandri, Riccardo; Jahani, Fatimeh; Qiu, Li; Marrink, Siewert J.; Havenith, Remco W. A.; Hummelen, Jan C.; Loi, Maria A.; Portale, Giuseppe
Abstract : The synergistic use of X-ray scattering and molecular dynamics simulations reveals the structure–property relationships of [60]fullerene derivatives with oligoethylene–glycol side chains. Abstract : For many years, fullerene derivatives have been the main n-type material of organic electronics and optoelectronics. Recently, fullerene derivatives functionalized with ethylene glycol (EG) side chains have been showing important properties such as enhanced dielectric constants, facile doping and enhanced self-assembly capabilities. Here, we have prepared field-effect transistors using a series of these fullerene derivatives equipped with EG side chains of different lengths. Transport data show the beneficial effect of increasing the EG side chain. In order to understand the material properties, full structural determination of these fullerene derivatives has been achieved by coupling the X-ray data with molecular dynamics (MD) simulations. The increase in transport properties is paired with the formation of extended layered structures, efficient molecular packing and an increase in the crystallite alignment. The layer-like structure is composed of conducting layers, containing of closely packed C60 balls approaching the inter-distance of 1 nm, that are separated by well-defined EG layers, where the EG chains are rather splayed with the chain direction almost perpendicular to the layer normal. Such a layered structure appears highly ordered and highly aligned with the C60 planes oriented parallel to the substrate in the thin film configuration. The order inside the thin film increases with the EG chain length, allowing the systems to achieve mobilities as high as 0.053 cm 2 V −1 s −1 . Our work elucidates the structure of these interesting semiconducting organic molecules and shows that the synergistic use of X-ray structural analysis and MD simulations is a powerful tool to identify the structure of thin organic films for optoelectronic applications.